2019
DOI: 10.4103/ijnmr.ijnmr_94_17
|View full text |Cite
|
Sign up to set email alerts
|

Transtheoretical model of health behavioral change: A systematic review

Abstract: Background: Transtheoretical model (TTM) is one of the most commonly used methods in behavioral change modeling. The aim of this study was to conduct a systematic review (SR) to determine research gaps with regard to this template with an emphasis on intervention for patients with chronic diseases (CDs). Materials and Methods: ISI-WOS, Scopus, PubMed, SID, and Magiran databases were examined systematically and on the basis of defined criteria. Titles, abstracts, and ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…To change a person's behavior, educators referring to the change process existing at each stage of behavior change where there are a decision-making process and changes in self-efficacy [9]. The application of the core construct of TTM can change the patient's behavior to become obedient [10,[24][25][26]. It is different from the results of the review by Friman et al [23] who found that the TTM-based education implemented was still able to change a person's behavior even though the intervention provided did not refer to a person's stages of change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To change a person's behavior, educators referring to the change process existing at each stage of behavior change where there are a decision-making process and changes in self-efficacy [9]. The application of the core construct of TTM can change the patient's behavior to become obedient [10,[24][25][26]. It is different from the results of the review by Friman et al [23] who found that the TTM-based education implemented was still able to change a person's behavior even though the intervention provided did not refer to a person's stages of change.…”
Section: Discussionmentioning
confidence: 99%
“…TTM has been widely used in changing patient behavior as evidenced by several previous reviews. Reviewed the effectiveness of TTM in the prevention of chronic disease [10], activity changes in self-management for people with DM Type 2 [11] and in changing physical activity behavior [12]. Meanwhile, hypertension itself is still limited to experimental research.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the cut-off points for time spent sitting as an indicator of frailty were more than 4.3 h/day for males and more than 5.5 h/day for females [52]. Assessment and intervention using TTM are useful for the management of various chronic diseases, such as T2D, hypertension, osteoporosis, or cancer, and other habits such as eating, sleeping, or smoking [53]. In this study, 53.8% of patients with poor glycemic control were in the precontemplation stage of TTM.…”
Section: Discussionmentioning
confidence: 99%
“…They focused on education about SHS and/or developing skills in women to avoid SHS exposure or negotiate with a family member, usually the husband. Five interventions were underpinned by a behaviour change framework, for example, the Transtheoretical Model of Change [ 26 ] and the Health Belief Model [ 27 ].…”
Section: Methodsmentioning
confidence: 99%